2017
DOI: 10.1002/jca.21606
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal photopheresis for graft versus host disease: Identifying a clinical pathway and associated resource utilization

Abstract: Extracorporeal photopheresis (ECP) is an established therapy for the treatment of graft-versus-host-disease (GVHD) following an allogeneic stem cell transplant. We performed a prospective analysis of patients receiving ECP treatment for GVHD to identify a clinical pathway and resource utilization of this process. The cohort included consecutive allogeneic stem cell recipients with GVHD. ECP was performed using the CELLEX Photopheresis System or the UVAR XTS Photopheresis System (Therakos, Inc, Exton, PA). A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…Similar differences between average treatment times, to those reported in this study and by Azar et al (120 minutes), 2 have been reported for CELLEX online procedures elsewhere (113, 135, and 117 minutes) 15,16 . The ability of other centers to perform only one offline ECP procedure per day, per bed, 14 is in line with the IEO, and highlights the potential time benefit of switching to integrated online ECP procedures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar differences between average treatment times, to those reported in this study and by Azar et al (120 minutes), 2 have been reported for CELLEX online procedures elsewhere (113, 135, and 117 minutes) 15,16 . The ability of other centers to perform only one offline ECP procedure per day, per bed, 14 is in line with the IEO, and highlights the potential time benefit of switching to integrated online ECP procedures.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the lack of a direct comparator group is a limitation of this study, as these analyses relied on comparisons with previously published data. However, the estimated median time to conduct one CELLEX ECP procedure reported by Azar et al was in line with recent observations 16 . The use of TDABC methodology is a strength of this study as this approach has a demonstrated ability to accurately capture the cost of care delivery, at the level of care processes, while having a small resource burden 13 .…”
Section: Discussionsupporting
confidence: 85%
“…In literature, there are detailed data on clinical efficacy, on the optimization of the patients’ paths and on the cost effectiveness of the inline procedure, while we found very few data about collection efficiency.…”
Section: Discussionmentioning
confidence: 87%
“…To date, the choice of inline or offline method is conditioned also by economic considerations. 29,30 In relation to ECP we have found many costeffectiveness analyses that take into account the use of resources calculated mainly in economic terms. The inline system is associated with higher set-up costs while the offline system is associated with higher personnel and time costs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand offline ECP does not require a dedicated device and therefore can be easily implemented in apheresis facility, it collects high cell yields but implies longer procedure and greater operator intervention. To date, the choice of inline or offline method is conditioned also by economic considerations 29,30 . In relation to ECP we have found many cost‐effectiveness analyses that take into account the use of resources calculated mainly in economic terms.…”
Section: Discussionmentioning
confidence: 99%